The ultimate guide to grandmas & grandpas! - Lloyd-Jones, Sally, 1960-; Emberley, Michael (New York : HarperCollins Publishers, 2008)
Offers charming advice, pointers, and helpful hints to grandchildren on how to best take care of their grandmas and grandpas by playing with them, sharing naps, and showing lots of love.
Horn Book.
Kirkus Review.
School Library Journal.
1.9
K-3
Keywords: Families -- Juvenile fiction; Grandparent and child -- Juvenile fiction; Family life -- Fiction; Grandparent and child -- Fiction; Family life -- Fiction; Grandparent-grandchild relationship -- Fiction